Eclectic Approach to Improve Software Engineering Students’ Research Article Writing Performance - Rumondang Miranda Marsaulina (Bulletin of Science Education, 2024)
Writing a research article in English to be published in good journals is crucial for university students. Prior studies assessing practices for the goal however focused mostly on scrutinizing single methods, whereas inquires of incorporated strategies or eclectic approach on improving a learner’s quality of English scientific writing genre still limited on the genres simpler than research article, as the higher scientific writing genre. This case study conducted using Qualitative method for data collection and analysis aims to explore how an eclectic approach has revamped scholarly texts written by 56 university students in Software Engineering learning English as a Foreign Language (EFL). The finding of this study revealed an eclectic approach merging Project-based Learning (PBL), Flower-Hayes’ process cognitive writing model and Holistic Flipped Classroom (HFC) could productively affect students’ writing products indicated from the increasing quality of their drafts throughout the writing stages. The conclusion is the eclectic approach integrating PBL, HFC and Flower and Hayes’ cognitive writing model can be considered to apply for other research article classes as long as the students have relatively similar English skill background with the participants of this study.